2012
DOI: 10.1159/000345227
|View full text |Cite
|
Sign up to set email alerts
|

Pure Hemi-Chorea Resulting from an Acute Phase of Contralateral Thalamic Lacunar Infarction: A Case Report

Abstract: Background: Thalamic lesions give rise to a variety of clinical syndromes such as pure sensory stroke, ataxic hemiparesis, and rarely involuntary movements including chorea. Generally and classically, lacunar infarction in the subthalamic nucleus has been regarded as the lesion mainly responsible for hemi-chorea and hemi-ballismus, on the basis of previous anatomical studies. Case Presentation: This report describes the case of an 81-year-old man who developed sudden-onset pure hemi-chorea in the right limbs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Of the immunological and neurochemical measures that were taken in the present study, IgG deposits in the thalamus are the only one which parallels the pattern of behavioral deficits in the food manipulation task (i.e., no IgG deposits – no motor deficit). In humans, damage to the thalamus caused by stroke can lead to choreic movements [56] , [57] and thalamic structural and functional alterations are correlated with motor symptoms in disorders such as SC, TS, Huntington’s disease, Parkinson’s disease and schizophrenia [58] [63] . In animals, different manipulations that disrupt thalamic functioning lead to motor alterations such as reduced grip strength, involuntary clasping movement and impairments in limb coordination and balance [64] , [65] .…”
Section: Discussionmentioning
confidence: 99%
“…Of the immunological and neurochemical measures that were taken in the present study, IgG deposits in the thalamus are the only one which parallels the pattern of behavioral deficits in the food manipulation task (i.e., no IgG deposits – no motor deficit). In humans, damage to the thalamus caused by stroke can lead to choreic movements [56] , [57] and thalamic structural and functional alterations are correlated with motor symptoms in disorders such as SC, TS, Huntington’s disease, Parkinson’s disease and schizophrenia [58] [63] . In animals, different manipulations that disrupt thalamic functioning lead to motor alterations such as reduced grip strength, involuntary clasping movement and impairments in limb coordination and balance [64] , [65] .…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases of chorea or ballism associated with isolated thalamic infarction have been reported. One study demonstrated that hypoperfusion of the STN and globus pallidus using a (99m) Tc-ethyl cysteinate dimer-single photon emission computed tomography associated with the development of chorea after stroke [ 26 ].…”
Section: Hyperkinetic Movement Disorders Induced By Lesions In the Bamentioning
confidence: 99%
“…1 Thalamic and subthalamic lesions are commonly known to cause hemichorea. 2,3 In this interesting case report, we describe a patient with hydrocephalus due to aqueductal stenosis which caused hemichorea in the immediate postoperative period due to subthalamic infarct. The infarct was due to posterior cerebral artery (PCA) involvement as a result of uncus herniation.…”
Section: Introductionmentioning
confidence: 97%